Prix du pétrole et degré de stabilité de l’OPEP - Ayoub, Antoine (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractThe stability of OPEC may be defined as the upholding of a high level of cohesion between the members of this organisation, in order to secure for the whole a certain level of bargaining power that everyone would think to be acceptable at a given time and in a given context. This level of cohesion is mainly estimated by the common will of members to apply rigorously a common strategy regarding the price-quantity of crude petroleum. In the long run, such a strategy would call for a common production plan in order to determine not only the total level of annual production, but also the quotas of each country, the price level and the rate of development of the capacity of production.The aim of this paper is to contribute to the bringing out of a problematic regarding such a production plan as a whole. The main topics are: (1) the necessity of OPEC, (2) the price determination of petroleum, (3) the question of the instability of a coalition. The analysis accounts for the fact that the petroleum sector produces a non-renewable resource, on the one hand, and for the environment and international constraints that the member countries of OPEC have to face in their development process, on the other hand.